Smart Printing Management System Using Structured Analysis - Tamilareson, Thivya; Abdullah, Noryusliza (International Journal of Advanced Science Computing and Engineering, 2020)
The Smart Printing Management System is an online printing ordering system. The purpose of developing this system is to take online printing orders in a much more efficient way from the customer so that the customer does not have to wait for a long time at the shop to print up their stuff. The system also provides printing templates design for each category of printings so that the customer can customize their own printing designs before they upload their material to order. The system also will manage the daily printing sales record from the customer which is the daily printing sales report will be saved in the system so that the shop will have proper records of the customer's sales every day. They can also view the daily printing sales report in a graph form where it will be easier to evaluate their daily sales. Moreover, the system also will manage the product stock as well which is the system will display "low stock" for the quantity of the product stock is less than 10. So the shop can know which the specific number of the item is currently available for the customer to purchase. Moreover, the admin also can add and edit the product stock whenever needed. Furthermore, this system also helps the shop to avoid product overstock and outages. The methodology that use to develop this system is the waterfall model.